Insecticidal Activity of Berberis Royleana: Various Extracts against Callosobruchus Maculatus - Salman, Muhammad; Rafique, Muhammad; Khan, Muddasir; Kainat; Khan, Hayat; Amin, Khalid; Roohullah; Ashraf, Waqas (BioScientific Review, 2022)
The residents of remote areas in developing countries mostly rely on traditional plants to cure different ailments. Berberis royleana is a rare species among the genus Berberis which commonly comprises 500 species distributed in Nepal, Afghanistan, Siberia, and other parts of the world. Berberis are used to make herbal medication to fight against infections, ocular trachoma, AIDS, and diarrhea. The current study was carried out to explore the in vitro insecticidal activity of B. royleana in various extracts by direct contact application process against the insect Callosobruchus maculatus. The maximum mortality rate of 60% was recorded by water fraction, whereas methanolic fraction had 50% mortality, n-Hexane had 40% mortality, while ethyl acetate and chloroform both had 30% mortality at 72 hours. Thus, this study indicated that from the medicinal point of view this specie is very significant, with a great potential for insecticidal activities against C. maculatus. It is further suggested that B. royleana could be used as a good insecticidal agent against dengue and malarial vectors. In addition, the side effects like toxicity could be addressed to avoid any mishaps.